2014
DOI: 10.1108/rsr-07-2013-0034
|View full text |Cite
|
Sign up to set email alerts
|

Information behaviour of humanities PhDs on an information literacy course

Abstract: Purpose – The aim of this paper is to examine whether an information literacy course/module is an appropriate intervention during the initial months of a humanities PhD, and if there is more that can be learned from the course participants that might provide a better understanding of their information behaviour. Design/methodology/approach – A questionnaire was distributed to new humanities PhD students prior to their attending the course. A second questionnaire was distributed to those who had completed the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
(61 reference statements)
0
14
0
1
Order By: Relevance
“…As a result, and in conjunction with new funding opportunities, humanities scholars are developing new information and working practices, including the creation of more formal and systematic research collaborations, according to Bulger et al (2011). Looking more closely at humanities doctoral students, Madden (2014) claim that the information-seeking needs of humanities PhD students are particularly varied and the challenges in the first year of their doctoral studies include defining and scoping their research topic, knowing which library resources are relevant to their research, making the best use possible of the technology, etc. Wu and Chen (2014) found that science and technology graduate students were more likely to use Google Scholar than their peers in humanities and social sciences; but humanities students were more likely to search by author name, title or keywords than in any other disciplines.…”
Section: Disciplinary Similarities and Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, and in conjunction with new funding opportunities, humanities scholars are developing new information and working practices, including the creation of more formal and systematic research collaborations, according to Bulger et al (2011). Looking more closely at humanities doctoral students, Madden (2014) claim that the information-seeking needs of humanities PhD students are particularly varied and the challenges in the first year of their doctoral studies include defining and scoping their research topic, knowing which library resources are relevant to their research, making the best use possible of the technology, etc. Wu and Chen (2014) found that science and technology graduate students were more likely to use Google Scholar than their peers in humanities and social sciences; but humanities students were more likely to search by author name, title or keywords than in any other disciplines.…”
Section: Disciplinary Similarities and Differencesmentioning
confidence: 99%
“…Of importance here is also the fact that doctoral students rarely choose their own doctoral research topic (Horlings and Gurney 2013) and are often inhibited by their lack of confidence in their research work ; this may have significant implications in doctoral students' engagement and informationseeking behaviours in the first stages of their doctoral studies. This is echoed in Madden (2014) who reported that most students in the humanities had changed their research topic in the first months of their doctoral studies, thus making the information-seeking process even more challenging. Not only their research topic is evolving in the first year but they also need to identify the range of resources that may become useful to their research.…”
Section: Supporting Doctoral Students In Their Information Seekingmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationships between information seeking and other variables, such as gender, [36][37][38] positions and the information needs, 39-41 discipline and education level, 42-45 prior knowledge, 46 personality traits, 47,48 information literacy, 42,49 and some sort of characteristics such as anxiety, 50,51 and uncertainty 52,53 have been measured by some scholars. The relationships between information seeking and other variables, such as gender, [36][37][38] positions and the information needs, 39-41 discipline and education level, 42-45 prior knowledge, 46 personality traits, 47,48 information literacy, 42,49 and some sort of characteristics such as anxiety, 50,51 and uncertainty 52,53 have been measured by some scholars.…”
Section: Related Workmentioning
confidence: 99%
“…Information seeking and its dimensions have been analyzed and measured in different disciplines and contexts. The relationships between information seeking and other variables, such as gender, [36][37][38] positions and the information needs, [39][40][41] discipline and education level, [42][43][44][45] prior knowledge, 46 personality traits, 47,48 information literacy, 42,49 and some sort of characteristics such as anxiety, 50,51 and uncertainty 52,53 have been measured by some scholars.…”
Section: Related Workmentioning
confidence: 99%